REDESIGN OF WET CAKE PACKAGING BASED ON INTELLIGENT PACKAGING AS A SPECIAL SOUVENIRPALEMBANG: CASE STUDY OF BR CAKE SHOP - Melati Pratama (Journal Hotspot, 2025)
BR is a cake shop in Palembang city that produces wet cakes, where wet cakes have a short shelf life so it is necessary to re-design the packaging. The purpose of this research is to identify kansei elements for packaging design, redesign packaging based on intelligent packaging and test consumer references to redesign. The method used is a quantitative approach with two stages, namely by distributing questionnaires to 67 respondents in stage 1 and 50 respondents in stage 2. The results show that interesting kansei elements for packaging design are attractive colors, distinctive designs, thick packaging materials, easy to read and provide expiration information. Packaging label redesign results based on kansei elements. Design 1 has the most preference with the highest score compared to other designs. Respondents gave higher ratings to Design 1 in terms of packaging label color (3.89), distinctive design (3.95), font (4.28) and expiration information (3.72).